Exposure to Ambient Air Pollution and Onset of Parkinson's Disease in a Large Cohort Study - Babak Jahanshahi; Duncan McVicar; Neil Rowland (Queen's University Belfast, Queen's Business School, 2025)
The emerging literature studying the association between exposure to ambient air pollution and Parkinson's Disease (PD) so far draws mixed conclusions. This study provides new evidence on this issue using data from a large and nationally representative cohort tracked over an extended period. We tracked a 28% representative sample of the Northern Ireland population between 2009 and 2016, with complete address records matched to annual average data on fine particulate matter (PM2.5) and nitrogen dioxide (NO2) concentrations at the 1km grid-square level, together with comprehensive information on PD medications dispensed over this period. We used these data to estimate associations between pollution exposure and PD onset as proxied by first receipt of PD medication, controlling extensively for potentially confounding factors at the neighbourhood, household and individual levels. Additionally, we estimated associations for sub-samples split by age and sex. There was no evidence of an association between medium-term PM2.5 or NO2 exposure and the risk of onset of PD in the overall cohort, nor among over-50s or samples split by sex. However, we found a positive association between early onset of PD (aged under 50 years as of 2011) and PM2.5 exposure, with more tentative evidence of an association with NO2 exposure. We discuss potential biological and nonbiological explanations for this age-related contrast.
Keywords: 330; Air pollution; PM2.5; NO2; Parkinson's Disease